A method for designing a lightweight high-strength composite material structure of an inland waterway vessel

CN122947259APending Publication Date: 2026-10-20SHAOXING LANCHENG SHIPBUILDING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611161035.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

当前内河船舶主流采用钢材结构,存在以下技术缺陷:一是钢材密度大,导致船舶自重过高,不仅增加推进系统能耗,降低载货/载客量,不符合内河航运“绿色低碳”的发展趋势;二是内河航道水深较浅、流速快、泥沙含量高,钢材结构易受泥沙磨损和淡水腐蚀,长期服役后易出现结构疲劳、锈蚀破损,维护周期短、维护成本高;三是传统钢材结构设计难以兼顾轻量化与高强度,若单纯减薄钢板厚度实现轻量化,会导致船体抗冲击、抗碰撞能力不足,无法适配内河航道狭窄、船舶密度高、易发生剐蹭碰撞的航行环境

Benefits of technology

实现船体结构轻量化与高比强度设计,显著降低航行阻力与能耗,提高燃料利用效率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1785722264621-000002
    Figure REF-OBJ-1785722264621-000002
  • Figure REF-OBJ-1785722264621-000003
    Figure REF-OBJ-1785722264621-000003
  • Figure REF-OBJ-1785722264621-000004
    Figure REF-OBJ-1785722264621-000004
Patent Text Reader

Abstract

This application relates to a lightweight, high-strength composite material structure design method for inland waterway vessels, comprising the following steps: collecting operating parameters of the inland waterway vessel and performing load analysis to determine structural weak points and performance requirements; selecting and optimizing a carbon fiber-glass fiber hybrid reinforced epoxy resin matrix composite system, adding nano-alumina and graphene functional fillers and verifying mechanical properties; designing a layered structure of "outer wear-resistant layer + middle structural strength layer + inner anti-corrosion layer," optimizing fiber laying direction and connection points; establishing a structural model and performing finite element simulation analysis and optimization verification; employing a vacuum-assisted resin transfer molding process and controlling molding parameters, implementing quality inspection; and iteratively optimizing design parameters through actual vessel verification to form a standardized scheme. This application achieves synergistic optimization of lightweight and high-strength inland waterway vessel structures, improving vessel wear resistance, reducing navigation energy consumption and maintenance costs, and extending structural fatigue life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of ship structural design, and in particular to a method for designing lightweight high-strength composite material structures for inland waterway vessels. Background Technology

[0002] As the core carrier of inland waterway transportation, the structural design of inland waterway vessels directly affects navigation efficiency, operating costs, and navigation safety. Currently, the mainstream inland waterway vessels adopt steel structures, which have the following technical defects: First, the high density of steel leads to excessive vessel weight, increasing propulsion system energy consumption and reducing cargo / passenger capacity, which is inconsistent with the "green and low-carbon" development trend of inland waterway transportation. Second, inland waterways are shallow, have high flow velocity, and high sediment content, making steel structures susceptible to silt abrasion and freshwater corrosion. After long-term service, they are prone to structural fatigue, rust, and damage, resulting in short maintenance cycles and high maintenance costs. Third, traditional steel structure design cannot balance lightweighting and high strength. Simply reducing the thickness of steel plates to achieve lightweighting leads to insufficient impact and collision resistance of the hull, making it unsuitable for the narrow inland waterways, high vessel density, and high risk of scraping and collisions.

[0003] In existing technologies, some ships attempt to use single composite materials to replace steel. Although this can achieve lightweighting, it suffers from problems such as insufficient strength, poor impact resistance, and easy delamination between layers, making it difficult to meet the structural load-bearing requirements of inland waterway vessels. In addition, some composite material structure designs are copied from seagoing vessel designs without fully considering the unique environment of inland waterways with shallow draft, strong abrasion, and low wind and waves. This results in excessive structural redundancy, insignificant lightweighting effect, or insufficient structural strength and short service life.

[0004] Therefore, considering the characteristics of the navigation environment of inland waterway vessels, designing a composite material structure design method that can achieve synergistic optimization of lightweight and high strength, while possessing excellent wear resistance and corrosion resistance, and adapting to the working conditions of inland waterways, has become an urgent need for the technological upgrading of inland waterway vessels. Summary of the Invention

[0005] To overcome the shortcomings of existing technologies, this application provides a design method for lightweight high-strength composite material structures for inland waterway vessels.

[0006] This application provides a lightweight, high-strength composite material structure design method for inland waterway vessels, which adopts the following technical solution: A method for designing lightweight, high-strength composite material structures for inland waterway vessels includes the following steps: Step 1: Collect operating parameters of inland waterway vessels, conduct load analysis, and determine structural weak points and performance requirements; Step 2: Select and optimize the composite material system, using carbon fiber-glass fiber hybrid reinforcement of epoxy resin matrix, adding functional fillers, and verifying the mechanical properties of the material; Step 3: Design a layered structure of "outer wear-resistant layer + middle structural strength layer + inner anti-corrosion layer", and optimize the fiber laying direction and connection design; Step 4: Establish a structural model, perform finite element simulation analysis and structural optimization, and verify whether the structural performance meets the design specifications; Step 5: Vacuum-assisted resin transfer molding process is used for molding parameter control and quality inspection; Step 6: Conduct on-ship verification, iteratively optimize design parameters, and form a standardized solution.

[0007] By adopting the above technical solutions, the self-weight of inland waterway vessels can be significantly reduced while ensuring high strength and safety, thereby improving the specific strength and specific stiffness of the structure, effectively reducing navigation resistance and energy consumption, and improving fuel utilization efficiency. The hybrid reinforcement design of carbon fiber and glass fiber takes into account both load-bearing capacity and cost control. At the same time, the introduction of nano-alumina and graphene enhances the wear resistance, fatigue resistance and crack propagation resistance of the materials. The layered structure design further improves the corrosion resistance and service life of the structure. By combining finite element simulation and actual ship verification, the structural performance is precisely optimized and the reliability is improved, meeting the long-term stable operation requirements under complex inland waterway conditions.

[0008] Optionally, in step 2, carbon fiber accounts for 30%-40% of the total mass of the reinforcement, glass fiber accounts for 60%-70%, and the functional filler includes 1%-3% nano-alumina and 0.5%-1% graphene, with a composite material density ≤1.5 g / cm³. 3 Tensile strength ≥ 800 MPa.

[0009] By adopting the above technical solutions, high specific strength and lightweight design can be achieved while controlling material costs. Carbon fiber and glass fiber work together to enhance the overall load-bearing and impact resistance, while nano-alumina and graphene improve wear resistance and crack resistance. This allows the composite material to have both high strength, durability and stability, meeting the needs of inland waterway vessels under complex working conditions.

[0010] Optionally, in step 3, the outer wear-resistant layer has a thickness of 1.5-2.5mm and nano-alumina is added; the middle structural strength layer has a thickness of 8-15mm, and the fiber laying direction is optimized according to the load distribution; the inner anti-corrosion layer has a thickness of 1.0-1.5mm and graphene is added.

[0011] By adopting the above technical solutions, the structural performance is optimized in layers. The outer wear-resistant layer enhances the resistance to erosion and wear, the middle strength layer enhances the load-bearing and fatigue resistance through directional laying, and the inner anti-corrosion layer effectively blocks media erosion and improves durability, thereby improving the overall structural reliability and service life.

[0012] Optionally, in step 4, finite element analysis software is used to simulate typical navigation conditions of inland waterway vessels. After optimization, the hull weight is reduced by 30%-40% compared to traditional steel structures, and the structural fatigue life is ≥20 years.

[0013] By adopting the above technical solutions, the structural stress and deformation can be accurately assessed and optimized under typical working conditions, significantly reducing the hull weight and improving structural efficiency, while extending fatigue life and service life, reducing maintenance frequency and operating costs, and ensuring the long-term safe and reliable operation of inland waterway vessels.

[0014] Optionally, in step 5, a vacuum-assisted resin transfer molding process is used, with a molding temperature of 60-80℃ and a molding pressure of 0.1-0.3MPa. After molding, ultrasonic non-destructive testing is performed.

[0015] By adopting the above technical solutions, high-quality molding and stable curing of composite material structures can be achieved, reducing the probability of bubble and defect generation and improving the material density and mechanical properties. Reasonable control of temperature and pressure is conducive to the resin fully impregnating the fiber and ensuring structural consistency. Combined with ultrasonic non-destructive testing, internal defects can be detected in time, improving the reliability and safety of finished products.

[0016] Optionally, in step 1, the operating parameters include the ship's design tonnage, length, beam, depth, and draft, as well as the current velocity, sediment content, water level fluctuation range, and temperature variation range of the navigation channel. The loads include static loads and dynamic loads. The static loads are the ship's own weight, cargo / passenger weight, and water pressure, while the dynamic loads are water flow impact force, sediment abrasion force, ship collision force, and wave impact force.

[0017] By adopting the above technical solutions, the stress and environmental conditions of inland waterway vessels in actual operation can be fully reflected, the accuracy and completeness of load analysis can be achieved, a reliable basis can be provided for structural design, weak parts can be identified and structural schemes can be optimized, and the safety, durability and adaptability of the hull under complex working conditions can be improved.

[0018] Optionally, in step 2, the carbon fiber is selected as T700 grade high-strength carbon fiber, and the glass fiber is selected as alkali-free glass fiber. Both are surface treated with silane coupling agent. The epoxy resin matrix is ​​also added with UV stabilizer and hydrolysis inhibitor to ensure that the mechanical properties of the composite material are retained at ≥90% under temperature cycling from -20℃ to 60℃.

[0019] By adopting the above technical solutions, the bonding strength between the fiber and resin interface is improved, the overall mechanical properties and stability of the composite material are enhanced, the resistance to ultraviolet aging and hydrolysis of the material is improved, and a high performance retention rate is maintained under temperature cycling environment, ensuring long-term reliability and durable use of the structure.

[0020] Optionally, in step 3, the fiber laying direction of the intermediate structural strength layer is optimized according to the load requirements of different parts of the hull. The bottom part adopts a 0° / 90° bidirectional laying, the side part adopts a ±45° oblique laying, and the deck part adopts a 0° / 45° / 90° multidirectional laying. The connection part preferably adopts an integrated molding process, and the parts that must be bolted are made of carbon fiber reinforced composite material bolts, and a reinforcing liner is added.

[0021] By adopting the above technical solutions, the direction of fiber stress in each part is matched with the actual load, giving full play to the advantages of material anisotropy and improving the structural load-bearing and fatigue resistance performance; integrated molding reduces weak links in the connection, and the design of reinforced bolts and liner plates improves the connection reliability and overall structural stability.

[0022] Optionally, in step 4, the typical navigation conditions include full load, shallow water navigation, and scrape collision. After optimization, the maximum hull deflection under full load is ≤ L / 1000 (L is the ship length), the collision resistance meets the requirement of no plastic deformation under 1.5 times the rated load impact, and the structural performance complies with the "Technical Rules for Inland Waterway Vessels" and the "Stability Specifications for Inland Waterway Vessels".

[0023] By adopting the above technical solutions, the hull structure is accurately checked and optimized under multiple typical working conditions, so that the deflection and impact resistance meet the specifications, plastic failure is avoided, the overall safety margin and stability are improved, and the reliable operation of the ship is ensured in complex navigation environments.

[0024] Optionally, in step 6, the actual ship sailing test period shall not be less than 6 months, and data on the sailing energy consumption, structural deformation, wear and corrosion of the prototype ship shall be collected. The performance differences of traditional steel ships shall be compared, and after iterative optimization, a standardized design scheme adapted to different tonnages and different inland waterway conditions shall be formed.

[0025] By adopting the above technical solutions, the structural performance is verified and corrected based on long-term real-ship data, the advantages in energy consumption, deformation and durability are quantified, design parameters are continuously optimized, the adaptability and reliability of the solution are improved, and a standardized design system that can be promoted is formed to meet the application needs of different tonnages and waterway conditions.

[0026] In summary, this application includes at least one of the following beneficial technical effects: Achieving lightweight and high specific strength design of the hull structure significantly reduces sailing resistance and energy consumption, and improves fuel utilization efficiency; By using carbon fiber-glass fiber hybrid reinforcement and functional filler modification, the structural load-bearing capacity, fatigue resistance and crack propagation resistance can be improved. The structure's wear resistance, corrosion resistance, and overall service life are improved through a layered design consisting of an outer wear-resistant layer, a middle structural strength layer, and an inner anti-corrosion layer. By combining finite element simulation with actual ship tests, structural parameters can be optimized and performance verified, thereby improving design reliability and engineering applicability. By using vacuum forming technology and non-destructive testing methods, the forming quality and structural consistency can be improved, the manufacturing defect rate can be reduced, and the long-term service safety can be enhanced. Attached Figure Description

[0027] Figure 1 This is a flowchart of an embodiment of this application.

[0028] Figure 2 This is a schematic diagram of the layered structure of an embodiment of this application.

[0029] Figure 3 This is a schematic diagram of the fiber laying direction and the hull part of this application.

[0030] Figure 4 This is a schematic diagram of the finite element analysis results under typical working conditions in this application.

[0031] Figure 5 This is a schematic diagram of the molding process, quality inspection, and actual ship verification. Detailed Implementation

[0032] The following is in conjunction with the appendix Figure 1-5 This application will be described in further detail.

[0033] This application discloses a lightweight high-strength composite material structure design method for inland waterway vessels. It is applicable to the hull structure design and optimization of various types of vessels, including inland waterway cargo ships, passenger ships, methanol-powered ships, electric ships, and unmanned intelligent ships. The method takes "operating condition driven - material collaboration - structural layering - numerical simulation - process forming - actual ship verification" as its core technical route, and achieves the unified design goal of lightweight and high reliability for inland waterway vessels under complex shallow water, high silt, and high-frequency scraping conditions.

[0034] Reference Figure 1 The overall design process of this application embodiment includes: inland waterway vessel operating condition parameter acquisition and navigation path modeling steps, load identification and weak area determination steps, composite material system design and performance optimization steps, layered structure and layup direction design steps, finite element simulation analysis and structural iterative optimization steps, molding process control and quality inspection steps, and actual ship verification and parameter feedback optimization steps. Each step forms a closed-loop optimization system through data iteration and performance feedback, thereby achieving continuous approximation of the optimal solution to the structural performance. In step 1, the operating parameters of inland waterway vessels are systematically collected and analyzed, and a typical navigation route model is constructed based on the characteristics of the route, such as... Figure 1As shown, the data includes basic parameters such as ship design tonnage, length, beam, depth, and draft. It also incorporates waterway environmental parameters, including current velocity distribution, water level fluctuation range, sediment content, waterway width variation, and temperature variation range. Further, it classifies and models the loads experienced by the ship during operation, categorizing them into two main types: static loads and dynamic loads. Static loads include the ship's own weight, cargo or passenger weight, and hydrostatic pressure; dynamic loads include water flow impact force, wave impact force, sediment erosion and wear force, and scraping and collision loads in narrow waterways. Through this load combination analysis, high stress concentration areas and potential fatigue weak points in the hull structure are identified, providing a basis for subsequent structural optimization. In step 2, the composite material system is selected and optimized. A carbon fiber and glass fiber hybrid reinforced epoxy resin matrix composite system is adopted, and nanoscale functional fillers are introduced to enhance performance. T700 grade high-strength carbon fiber is selected to improve the overall structural stiffness and tensile strength; alkali-free glass fiber is selected to improve impact toughness and cost-effectiveness. The two fibers are optimized in a specific mass ratio, with carbon fiber accounting for 30%-40% and glass fiber accounting for 60%-70%. Furthermore, 1%-3% nano-alumina and 0.5%-1% graphene are added to the resin matrix to improve the material's wear resistance, thermal conductivity, and crack propagation resistance. Meanwhile, the addition of UV stabilizers and anti-hydrolysis agents to the resin system enhances the composite material's environmental adaptability in complex inland river environments. Verification has shown that the density of this composite material system is ≤1.5 g / cm³. 3 Tensile strength ≥800MPa, mechanical property retention rate ≥90% under cyclic conditions from -20℃ to 60℃, meeting the requirements for long-term service in inland waterways; In step 3, as Figure 2 and Figure 3 As shown, the hull structure is designed with layers and optimized fiber layup, employing a three-layer composite structure system: an outer wear-resistant layer, a middle structural strength layer, and an inner anti-corrosion layer. The outer wear-resistant layer, with a thickness of 1.5-2.5 mm, is mainly used to resist erosion from mud and sand and abrasion, and nano-alumina particles are introduced to improve surface hardness and wear resistance. The middle structural strength layer, with a thickness of 8-15 mm, is the main load-bearing layer, and its structural strength is maximized through optimized fiber layup angles. The inner anti-corrosion layer, with a thickness of 1.0-1.5 mm, is mainly used to prevent water corrosion and chemical erosion, and graphene is added to enhance barrier properties and corrosion resistance. In the intermediate structural strength layer, differentiated ply designs are implemented according to different stress areas of the hull. The bottom area adopts a 0° / 90° bidirectional ply structure to improve longitudinal bending stiffness and overall load-bearing capacity; the side area adopts a ±45° oblique ply structure to enhance shear and impact resistance; the deck area adopts a 0° / 45° / 90° multidirectional hybrid ply structure to balance structural stability under multidirectional loads. For hull connection parts, integrated molding process is preferred to reduce stress concentration; for parts that must use mechanical connections, carbon fiber reinforced composite bolts are used, along with reinforcing plates to improve local load-bearing capacity. In step 4, as Figure 4 As shown, a three-dimensional finite element analysis model of the hull is established, and numerical simulation and optimization analysis of the structure are performed. The finite element model is discretized using composite laminated shell elements. Combined with the actual hull geometry and material parameters, the stress state under typical navigation conditions is simulated, including full-load navigation, shallow water navigation and scraping collision conditions. Simulation results show that, under optimized structural design conditions, the overall stress distribution of the hull is more uniform, stress concentration is significantly reduced, the maximum equivalent stress is controlled within the allowable stress range of the material, the maximum hull deflection meets the design requirement of L / 1000 (L is the length of the ship), the overall structural stiffness meets the technical specifications for inland waterway vessels, and through mass optimization design, the hull weight is reduced by 30%-40% compared with traditional steel structures, effectively improving cargo carrying capacity and navigation economy. In the fatigue performance analysis, the cumulative damage of the structure was evaluated by cyclic load simulation. The results showed that the fatigue life of the structure can reach more than 20 years, which meets the long-term operation requirements of inland waterway vessels. In the collision resistance performance analysis, the structure did not undergo plastic deformation under the impact of 1.5 times the rated load, and has a good safety margin. In step 5, as Figure 5 As shown, a vacuum-assisted resin transfer molding (VARTM) process was used to prepare the composite material structure. During the molding process, the resin was fully impregnated and evenly distributed on the fibers by controlling the vacuum level, resin flow rate, and curing temperature. The molding temperature was controlled at 60-80℃, and the molding pressure was controlled at 0.1-0.3MPa to ensure the quality of interlayer bonding and structural density. After molding, the structure underwent quality inspection. Ultrasonic non-destructive testing was used to detect internal defects, including pores, delamination, and resin-rich areas. Infrared thermal imaging technology was also used for rapid scanning and inspection of large-area structures. Key load-bearing components underwent mechanical property testing, including tensile, bending, and shear performance tests, to ensure batch consistency and structural reliability. In step 6, the optimized composite material structure is applied to the actual ship construction and sea test. The test content includes speed performance, energy consumption index, vibration and noise level and structural health monitoring. In actual navigation, compared with traditional steel structure ships, the composite material hull increases the speed by about 8%-15% under the same power conditions, reduces the unit energy consumption by about 10%-20%, and significantly reduces vibration transmission, thereby improving the comfort of ship operation and the stability of equipment. During actual ship operation, a structural health monitoring system is deployed to monitor strain, vibration, and fatigue cumulative damage in key components in real time. The data is then fed back to the design model to achieve further iterative optimization of structural parameters, forming a standardized design database that provides a reference for the design of similar ships in the future.

[0035] The embodiments of this application achieve a comprehensive improvement in the lightweight, high strength, wear resistance and corrosion resistance of composite material structures for inland waterway vessels through a multi-dimensional collaborative design method, including multi-scale material design, layered structure optimization, ply direction control, finite element simulation verification and actual ship feedback optimization. It has significant engineering application value and promotion prospects.

[0036] The implementation principle of the lightweight high-strength composite material structure design method for inland waterway vessels in this application embodiment is as follows: Based on the core idea of ​​"optimal structural performance design driven by typical service conditions of inland waterway vessels," this method systematically models and couples the complex loads, non-uniform mechanical responses of materials, and layered load-bearing mechanisms in the actual navigation environment to achieve synergistic optimization design of the hull structure between lightweight and high strength. Firstly, at the load mechanism level, this method, based on typical conditions such as shallow water, high sediment content, narrow channels, and frequent collisions in inland waterways, uniformly models the static and dynamic loads experienced by the vessel during navigation. Static loads originate from the hull's own weight, cargo or passenger loads, and hydrostatic pressure; dynamic loads include water flow impact, wave disturbance, and sediment scouring. Transient impacts such as wear and scratches are assessed by constructing load spectra, combining and equivalencing loads under different voyage conditions to accurately identify high-stress and fatigue-sensitive areas in the hull structure. Secondly, at the material reinforcement mechanism level, a hybrid epoxy resin-based composite material system reinforced with carbon fiber and glass fiber is employed. The synergistic effect of different fiber materials achieves complementary performance: carbon fiber provides high specific strength and high specific stiffness to withstand tensile and bending stresses in the main load direction; glass fiber provides high toughness and impact resistance to absorb transient impact energy and inhibit crack propagation. Furthermore, the introduction of functional fillers such as nano-alumina and graphene further enhances the material's wear resistance, crack propagation resistance, and interfacial bonding performance, improving the overall service stability of the composite material. Furthermore, at the level of structural layered load-bearing mechanism, a three-layer composite structural system consisting of an outer wear-resistant layer, a middle structural strength layer, and an inner anti-corrosion layer is constructed to achieve functional zoning and load-level transfer. The outer wear-resistant layer mainly resists erosion by mud and sand and mechanical wear, the middle structural strength layer bears the main structural load and maximizes mechanical performance through fiber layup direction optimization, and the inner anti-corrosion layer is used to block water erosion and chemical corrosion. The stress is continuously transferred between the layers through interface reinforcement design to avoid interlayer delamination and interface failure. At the level of structural optimization mechanism, multi-condition mechanical response analysis of composite material structure is carried out through finite element numerical simulation. The structural stress distribution, deformation characteristics and safety factor are used as optimization objective functions. By adjusting the fiber layup angle, layer thickness distribution and material ratio, a multi-objective optimization balance between structural stiffness, strength and weight is achieved, and structural weight reduction design is achieved under the premise of meeting the specification requirements. At the manufacturing mechanism level, a vacuum-assisted resin transfer molding process is employed, which allows the resin to uniformly impregnate the fiber preform under negative pressure, improving the density and interfacial bonding quality of the composite material. Furthermore, process parameters (such as temperature, pressure, and flow rate) are controlled to reduce the probability of porosity and defects. Simultaneously, non-destructive testing techniques are used to assess the quality of the molded structure, ensuring structural consistency and service reliability. Finally, at the level of system iterative optimization mechanism, real navigation data is obtained through actual ship tests and compared with simulation results. The material ratio, ply scheme and structural parameters are then corrected in reverse to realize a closed-loop optimization system of design-simulation-manufacturing-verification, so that the structural design gradually approaches the optimal engineering solution.

[0037] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.

Claims

1. A method for designing lightweight, high-strength composite material structures for inland waterway vessels, characterized in that: Includes the following steps: Step 1: Collect operating parameters of inland waterway vessels, conduct load analysis, and determine structural weak points and performance requirements; Step 2: Select and optimize the composite material system, using carbon fiber-glass fiber hybrid reinforcement of epoxy resin matrix, adding functional fillers, and verifying the mechanical properties of the material; Step 3: Design a layered structure of "outer wear-resistant layer + middle structural strength layer + inner anti-corrosion layer", and optimize the fiber laying direction and connection design; Step 4: Establish a structural model, perform finite element simulation analysis and structural optimization, and verify whether the structural performance meets the design specifications; Step 5: Vacuum-assisted resin transfer molding process is used for molding parameter control and quality inspection; Step 6: Conduct on-ship verification, iteratively optimize design parameters, and form a standardized solution.

2. The method according to claim 1, characterized in that, In step 2, carbon fiber accounts for 30%-40% of the total mass of the reinforcement, glass fiber accounts for 60%-70%, and the functional fillers include 1%-3% nano-alumina and 0.5%-1% graphene. The density of the composite material is ≤1.5 g / cm³. 3 Tensile strength ≥ 800 MPa.

3. The method according to claim 1, characterized in that, In step 3, the outer wear-resistant layer is 1.5-2.5mm thick and contains nano-alumina; the middle structural strength layer is 8-15mm thick and the fiber laying direction is optimized according to the load distribution; the inner anti-corrosion layer is 1.0-1.5mm thick and contains graphene.

4. The method according to claim 1, characterized in that, In step 4, finite element analysis software is used to simulate typical navigation conditions of inland waterway vessels. After optimization, the hull weight is reduced by 30%-40% compared with traditional steel structures, and the structural fatigue life is ≥20 years.

5. The method according to claim 1, characterized in that, In step 5, a vacuum-assisted resin transfer molding process is used, with a molding temperature of 60-80℃ and a molding pressure of 0.1-0.3MPa. After molding, ultrasonic non-destructive testing is performed.

6. The method according to claim 1, characterized in that, In step 1, the operating parameters include the ship's design tonnage, length, beam, depth, and draft, as well as the current velocity, sediment content, water level fluctuation range, and temperature variation range of the navigation channel. The loads include static loads and dynamic loads. The static loads are the ship's own weight, cargo / passenger weight, and water pressure, while the dynamic loads are water flow impact force, sediment abrasion force, ship collision force, and wave impact force.

7. The method according to claim 1, characterized in that, In step 2, the carbon fiber is selected as T700 grade high-strength carbon fiber, and the glass fiber is selected as alkali-free glass fiber. Both are surface treated with silane coupling agent. The epoxy resin matrix is ​​also added with UV stabilizer and hydrolysis inhibitor to ensure that the mechanical properties of the composite material are retained at ≥90% under temperature cycling from -20℃ to 60℃.

8. The method according to claim 1, characterized in that, In step 3, the fiber laying direction of the intermediate structural strength layer is optimized according to the load requirements of different parts of the hull. The bottom part adopts 0° / 90° bidirectional laying, the side part adopts ±45° oblique laying, and the deck part adopts 0° / 45° / 90° multidirectional laying. The connection parts are preferably made of integrated molding process. The parts that must be bolted are made of carbon fiber reinforced composite material bolts and reinforced lining plates are added.

9. The method according to claim 1, characterized in that, In step 4, the typical navigation conditions include full load, shallow water navigation, and scrape collision. After optimization, the maximum hull deflection under full load is ≤ L / 1000 (L is the ship length), the collision resistance meets the requirement of no plastic deformation under 1.5 times the rated load impact, and the structural performance complies with the "Technical Rules for Inland Waterway Vessels" and the "Stability Specifications for Inland Waterway Vessels".

10. The method according to claim 1, characterized in that, In step 6, the actual ship sailing test period shall not be less than 6 months. Data on the ship's sailing energy consumption, structural deformation, wear and corrosion shall be collected. The performance differences of traditional steel ships shall be compared and iteratively optimized to form a standardized design scheme that is suitable for different tonnages and different inland waterway conditions.